Organizational barriers to transforming large finance corporations - Cao, Sam (Ruiqing),Iansiti, Marco (CESifo, 2022)
This paper studies the impact of technological architecture around data storage and processing on the performance of large financial corporations after being exposed to more stringent data privacy regulations. A modular approach to cloud adoption - which reflects in the lack of data interoperability and reliance on microservices architecture - significantly constrains corporations' ability to adapt after the GDPR became enforceable. We hypothesize that a modular approach to cloud adoption leads to uncontrolled scaling and data silos that hinder coordination and regulatory compliance. Using a difference-in-differences regression design, we find that establishment revenues lower by 30% among corporations substantially exposed to GDPR. Other corporations do not experience similar losses. We also find evidence consistent with theory using two alternative measures based on cloud vendor configurations.
10419/271786
Keywords: Graue Literatur; technological architecture; cloud computing; ecosystem; GDPR; organisation design